Postdialysis Hemolysis With Acute Pigmentation After Oral Nimesulide in a Chronic Hemodialysis Patient - Dogukan, Ayhan; Aygen, Bilge; Guler, Murat; Ozalp, Goksel; Gunal, Ali Ihsan; Celiker, Huseyin (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2007)
Acute hemolysis is well recognized as a complication of hemodialysis treatment. Causes of hemolysis are multiple and include mechanical red blood cell destruction and chemical hemolysis. These etiologies should be differentiated from other forms of hemolysis that can occur without a causal relationship to hemodialysis, including the autoimmune hemolytic anemias, microangiopathic hemolysis and hemolytic uremic syndromes. This report describes a patient who developed sudden deepening of pigmentation after hemodialysis treatment. Investigation indicated that the cause was severe hemolysis most probably due to the nonsteroidal anti inflammatory drug, nimesulide.
Keywords: hemodialysis; hemolysis; nimesulide